Mediasi Pengetahuan Islam Modern melalui Layanan Perpustakaan di Jepang - Umar, Touku; Haif, Abu (UPT Perpustakaan UIN Alauddin Makassar, 2026)
This study examines the mediation of modern Islamic knowledge through library services in Japan as a response to the increasing demand for Islamic information within a multicultural and predominantly non-Muslim society. This topic is significant because libraries play a strategic role not only as information centers but also as spaces for intercultural and interreligious dialogue in fostering a moderate, inclusive, and academically grounded understanding of Islam. This research employs a literature review method by examining scholarly sources such as books, journal articles, research reports, and library policy documents relevant to modern Islam and library services in Japan. Data collection was conducted through a systematic literature search, source selection based on relevance and credibility, and thematic categorization of the reviewed materials. The data were analyzed using content analysis to identify patterns, concepts, and forms of mediation of Islamic knowledge within library services. The findings indicate that the development of multilingual collections, the provision of academic resources on modern Islam, and information literacy programs are the main strategies used by libraries to mediate Islamic knowledge. Libraries in Japan contribute to presenting a contextual and scholarly understanding of Islam.